Maintenance of Measles Elimination Status in the United States for 20 Years Despite Increasing Challenges. (26th November 2021) - Mathis, Adria D; Clemmons, Nakia S; Redd, Susan B; Pham, Huong; Leung, Jessica; Wharton, Adam K; Anderson, Raydel; McNall, Rebecca J; Rausch-Phung, Elizabeth; Rosen, Jennifer B; Blog, Debra; Zucker, Jane R; et al.
Abstract: Background: Measles elimination (interruption of endemic measles virus transmission) in the United States was declared in 2000; however, the number of cases and outbreaks have increased in recent years. We characterized the epidemiology of measles outbreaks and measles transmission patterns after elimination to identify potential gaps in the US measles control program. Methods: We analyzed national measles notification data from 1 January 2001 to 31 December 2019. We defined measles infection clusters as single cases (isolated cases not linked to additional cases), 2-case clusters, or outbreaks with ≥3 linked cases. We calculated the effective reproduction number ( R ) to assess changes in transmissibility and reviewed molecular epidemiology data. Results: During 2001–2019, a total of 3873 measles cases, including 747 international importations, were reported in the United States; 29% of importations were associated with outbreaks. Among 871 clusters, 69% were single cases and 72% had no spread. Larger and longer clusters were reported since 2013, including 7 outbreaks with >50 cases lasting >2 months, 5 of which occurred in known underimmunized, close-knit communities. No measles lineage circulated in a single transmission chain for >12 months. Higher estimates of R were noted in recent years, although R remained below the epidemic threshold of 1. Conclusions: Current epidemiology continues to support the interruption of endemic measles virus transmission in the United States. However, larger and longer outbreaks in recent postelimination years and emerging trends of increased transmission in underimmunized communities emphasize the need for targeted approaches to close existing immunity gaps and maintain measles elimination. Abstract : Althoughmeasles elimination has been maintained in the United States for the past 20 years, emerging trends of increased transmission related to clustering of unvaccinated persons highlight the need to close existing immunity gaps and the importance of outbreak preparedness.